Territorializing Internet: WhatsApp use in Andean Argentina - Di Tullio, Martina; Gómez-Cruz, Edgar (AoIR Selected Papers of Internet Research, 2026)
Internet studies have predominantly focused on the most recent platforms, leaving out many different ways to use internet that become invisible for mainstream studies. At the same time, the majority of internet studies are centered on urban contexts, leaving out populations and their use of internet in rural territories. WhatsApp has emerged as one of the most widely used apps, particularly in the Global South. However, its integration into rural and Indigenous contexts in Latin America remains relatively unexplored. The Jujuy Puna, situated in NW Argentina and home to Quechua communities, recently gained internet connectivity through state initiatives. As a result, the internet has become part of these communities’ daily lives, with WhatsApp, in particular, becoming a vital infrastructure integrated into various aspects of everyday activities, including communication, governance, economy, health, and spirituality. Drawing on ethnographic fieldwork in two villages, Cusi Cusi and Lagunillas del Farallón, this paper examines the use of WhatsApp in these communities. The objective is to highlight the socio-technical adaptability processes through which the uses of WhatsApp in the Jujuy Puna expand communication practices and ways of being that are specific to the local modes of relating to others and to technology. The ethnographic approach enables us to trace continuities that shape the appropriation of WhatsApp in accordance with regional Andean ways of inhabiting and understanding the world. Our aim is to understand WhatsApp from the perspective of the territory, hoping to encourage more diverse dialogues between Latin American anthropology, communication, and internet studies.